(untitled) (Journal of Nobel Medical College, 2021)
Background: Low-income countries like Nepal experience a double disease burden infectious diseases risk as well as rising incidence of non-communicable diseases .The present cross sectional study assesses the prevalence of overweight and associated factors in ward no. 1 and 3 of Tankisinuwari VDC, Morang. Materials and Methods: A Community based cross sectional study was conducted in ward no. 1 and 3 of Tankisinuwari VDC, Morang. Total 152 (10%) households were selected by systematic random sampling technique and then 590 individuals (male 323 and female 267), with the age ranging from 10 to 70 years were included in the study. Measurement of weight and height was done by calibrated standard weighing scale and measuring tape. Results: The prevalence of overweight was 16.1% which was significantly more among male (11.5%) than in female ( 4.6%) while prevalence of obesity was 2.5% , which was significantly more among female (2.2%), than male (0.3)%, P<0.05.The prevalence of overweight was seen more in the age group ≥50 years (7.1%) and obesity was seen more in age group 30-49 years ((2.0%). The prevalence of overweight (13.9%) and obesity (2.4%) among married group were found significantly more than unmarried population where the prevalence of overweight and obesity were (2.2%) and (0.2%) respectively, P<0.05. Prevalence of obesity among those who had short sleep of 6 hours (1.4%) and overweight (3.9%) was observed which significantly more than among those who slept 7 hour or 8 hour. P=0.013. Conclusion: The role of risk factors in development of obesity like short sleep and long sleep duration, physical inactivity and mode of transport were observed to be associated with overweight and obesity. Demographic factors like age, gender and marital status was found to be associated with overweight and obesity.